2017
DOI: 10.1038/s41598-017-15778-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential overexpression of SERPINA3 in human prion diseases

Abstract: Prion diseases are fatal neurodegenerative disorders with sporadic, genetic or acquired etiologies. The molecular alterations leading to the onset and the spreading of these diseases are still unknown. In a previous work we identified a five-gene signature able to distinguish intracranially BSE-infected macaques from healthy ones, with SERPINA3 showing the most prominent dysregulation. We analyzed 128 suitable frontal cortex samples, from prion-affected patients (variant Creutzfeldt-Jakob disease (vCJD) n = 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 58 publications
(60 reference statements)
4
54
0
Order By: Relevance
“…On the one hand, SerpinA1 may play a protective role as a molecular chaperone that prevents amyloid fibril formation and its O‐linked sialylation could act as a suppressor of pathogenetic self‐hyperphosphorylation as sialylation and phosphorylation share similar motifs . Alternatively, SerpinA1 post‐translational modifications might be detrimental by (1) blocking specific serine proteases and lead to impaired clearance of prion‐like proteins or (2) promoting the formation of a misfolded and self‐aggregate‐prone structure of SerpinA1 . On another issue, SerpinA1 is emerging as an important modulator of neuroinflammation …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, SerpinA1 may play a protective role as a molecular chaperone that prevents amyloid fibril formation and its O‐linked sialylation could act as a suppressor of pathogenetic self‐hyperphosphorylation as sialylation and phosphorylation share similar motifs . Alternatively, SerpinA1 post‐translational modifications might be detrimental by (1) blocking specific serine proteases and lead to impaired clearance of prion‐like proteins or (2) promoting the formation of a misfolded and self‐aggregate‐prone structure of SerpinA1 . On another issue, SerpinA1 is emerging as an important modulator of neuroinflammation …”
Section: Discussionmentioning
confidence: 99%
“…6 On another issue, recent studies showed that SerpinA3, another member of the serpin family, is significantly upregulated in brains and CSF of patients with prion disease, both at the mRNA and at the protein level, although to a different extent for each pathological subtype. 23,27,28 However, all these studies focused on the levels of total Relative peak area analysis for sCJD and FTLD subtypes. (A) Normalized peak area analysis of peak 0 for the sCJD subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Padmanabhan et al reported that anti‐chymotrypsin induces tau phosphorylation in neurons. In various neurological diseases, the expression of SERPINA3N in the brain has been found to be significantly upregulated . Recent studies have also shown that SERPINA3N is clearly related to many inflammation‐related diseases, such as hypothalamic inflammation, retinal neuroinflammation, allergic airway inflammation, myocarditis, and atherosclerosis .…”
Section: Discussionmentioning
confidence: 99%
“…Serpina3n encodes anti‐chymotrypsin, which is a widely expressed member of the serpin superfamily and has recently been recognized as a key component of the inflammatory response in the brain . In many neurological diseases, anti‐chymotrypsin in the brain has been found to be markedly upregulated . Serpina3n was also reported as a highly expressed gene in persistently active astrocytes .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation